Catechol inhibits epidermal growth factor-induced epithelial-to-mesenchymal transition and stem cell-like properties in hepatocellular carcinoma cells - Lim, Won-Chul; Kim, Hyunhee; Kim, Young-Joo; Jeon, Bu-Nam; Kang, Hee-Bum; Ko, Hyeonseok (NATURE PUBLISHING GROUP, 2020)
Epithelial-mesenchymal transition (EMT) is a major cellular process in which epithelial cells lose cell polarity and cell-cell adhesion and become motility and invasiveness by transforming into mesenchymal cells. Catechol is one of the natural compounds present in fruits and vegetables and has various pharmacological and physiological activities including anti-carcinogenic effects. However, the effects of catechol on EMT has not been reported. Epidermal growth factor (EGF) is one of the growth factors and is known to play a role in inducing EMT. The present study showed that catechol suppressed not only the morphological changes to the mesenchymal phenotype of epithelial HCC cells, but also the reduction of E-cadherin and the increment of Vimentin, which are typical hallmark of EMT. In addition, catechol suppressed EMT-related steps such as migration, invasion, anoikis resistance acquisition, and stem cell-like characterization through the EGFR-AKT-ERK signaling pathway during liver cancer metastasis. Therefore, these results suggest that catechol may be able to regulate the early metastasis of liver cancer in vitro.
Keywords: MATRIX METALLOPROTEINASE-2; MOLECULAR-MECHANISMS; CANCER; ACTIVATION; INVASION; EGFR; PROLIFERATION; PLASTICITY; PATHWAYS; TISSUE